How does internet usage influence on social capital, connectedness, success and well-being of grassroots level inventors in Sri Lanka? - Wickramasinghe, Chaminda Nalaka; Ahmad, Nobaya (2014)
Internet has been recognized as the world largest knowledge depositary. Therefore, there is overwhelming expectation over the Internet to be influenced the social and technological development of marginalized communities of less developed countries. However there were no published studies that investigate the nature of the innovation systems and the impact of internet on the inventors in developing countries. Therefore, the existing knowledge of how the internet usage of influence on social capital, connectedness, success and subjective well-being of inventive community in developing countries is vague. Present study explores the influence of the internet usage on social capital, community connectedness, inventive achievements and subjective well-being of the grassroots level inventive community of Sri Lanka. Findings suggest that internet has been significantly influenced on the social capital, connectedness and subjective well-being of grassroots level inventors in Sri Lanka. However, internet usage is not significantly influence on the objective inventive achievements of the inventors.